2022
DOI: 10.1515/jpm-2021-0562
|View full text |Cite
|
Sign up to set email alerts
|

Nasal bone in fetal aneuploidy risk assessment: are they independent markers in the first and second trimesters?

Abstract: Objectives In the mid-trimester ultrasound, nasal bone (NB) length can be used to correct the a priori risk for trisomy 21. Our study aims to evaluate if there is a correlation between an absent NB in the first trimester and a hypoplastic NB in the second trimester. Methods Our two year retrospective analysis of data derived from routine clinical practice. Single euploid fetuses were included. The NB was assessed in both trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…[16][17][18][19][20] The current prospective observational study performed to determine the diagnostic validity of second trimester fetal A retrospective study performed by Bernardeco et al reported that the NBL in the first and second trimesters was associated with aneuploidy. 21 A study conducted in the Thai population reported statistically significant differences in the NBL, PNT, and NBL/PNT ratio between normal and DS fetuses, which is in consonance with the current study reports. 22 A retrospective study by Vos et al in the Netherlands reported the correlation coefficient of NBL and PNT against GA as 0.69 and 0.74, which is closely aligned with the findings of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…[16][17][18][19][20] The current prospective observational study performed to determine the diagnostic validity of second trimester fetal A retrospective study performed by Bernardeco et al reported that the NBL in the first and second trimesters was associated with aneuploidy. 21 A study conducted in the Thai population reported statistically significant differences in the NBL, PNT, and NBL/PNT ratio between normal and DS fetuses, which is in consonance with the current study reports. 22 A retrospective study by Vos et al in the Netherlands reported the correlation coefficient of NBL and PNT against GA as 0.69 and 0.74, which is closely aligned with the findings of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Absence or hypoplasticity of NB has been considered as one of the strongest ultrasound markers for Down’s syndrome and other chromosomal abnormalities in the first and second trimester in previous studies ( Canda et al, 2017 ; Du Y et al, 2018 ; Bernardeco et al, 2022 ). In our present study, 27.81% (89/230) of fetuses with NBA were found to have chromosomal abnormalities, including 53 cases of trisomy 21, which was the most common type of chromosomal aneuploidy and accounted for 59.55% (53/89) of all abnormalities detected.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the fetuses evaluated as nasal bone aplasia in the first trimester ultrasonography can be considered as nasal bone hypoplasia cases in the second trimester ultrasonography. 7 For this reason, while it is recommended to evaluate the presence of nasal bone in the first trimester in all pregnant women, nasal bone measurement is recommended in the second trimester ultrasonography. Invasive procedures are also recommended for definitive diagnosis of chromosomal abnormalities in the absence or hypoplasia of nasal bone.…”
Section: Second Trimester Fetal Nasal Bone Length Measurement: a Sing...mentioning
confidence: 99%